2017
DOI: 10.1111/acem.13085
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Enrolling Children Into Traumatic Brain Injury Trials: An Observational Study

Abstract: Objectives: In preparation for a clinical trial of therapeutic agents for children with moderate-to-severe blunt traumatic brain injuries (TBIs) in emergency departments (EDs), we conducted this feasibility study to (1) determine the number and clinical characteristics of eligible children, (2) determine the timing of patient and guardian arrival to the ED, and (3) describe the heterogeneity of TBIs on computed tomography (CT) scans. Methods:We conducted a prospective observational study at 16 EDs of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Parents of children resuscitated from cardiac arrest n = 12, parents of children in PICU n = 11, PICU nurses n = 13, physicians n = 10, administration n = 10 Concluded prospective informed consent was not feasible and endorsed exception of IC if have an explicit opportunity to decline participation Proposed intervention was to be instituted within 30 min, therefore had more time that other scenarios Scholefield, 2013[ 31 ] 28 UK EDs “appropriateness” of DC Web-based survey 77 Emergency Medicine consultants 74% approved the use of deferred consent in such a trial. Limited data relevant to review question (single question) Stanley, 2017[ 24 ] 16 level I paediatric trauma centre EDs in USA Describe the clinical characteristics, and timing of parent guardian arrival. Prospective, observational study 295 children with blunt head trauma with Glasgow Coma Scale (GCS) scores of 3–12 (i.e., moderate-to-severe TBI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents of children resuscitated from cardiac arrest n = 12, parents of children in PICU n = 11, PICU nurses n = 13, physicians n = 10, administration n = 10 Concluded prospective informed consent was not feasible and endorsed exception of IC if have an explicit opportunity to decline participation Proposed intervention was to be instituted within 30 min, therefore had more time that other scenarios Scholefield, 2013[ 31 ] 28 UK EDs “appropriateness” of DC Web-based survey 77 Emergency Medicine consultants 74% approved the use of deferred consent in such a trial. Limited data relevant to review question (single question) Stanley, 2017[ 24 ] 16 level I paediatric trauma centre EDs in USA Describe the clinical characteristics, and timing of parent guardian arrival. Prospective, observational study 295 children with blunt head trauma with Glasgow Coma Scale (GCS) scores of 3–12 (i.e., moderate-to-severe TBI).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies specifically addressed whether prospective informed consent was feasible [ 19 , 24 ]. A study conducted by the Pediatric Emergency Care Applied Research Network (PECARN), exploring the feasibility of various aspects of a study of moderate to severe traumatic brain injury, found that parents and guardians are often not available within the narrow therapeutic window of investigational therapies [ 24 ]. While children often arrived within an hour or two of injury, most parents and guardians did not arrive until 2 to 3 h or later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unavailability of parents or legal guardians to provide written informed consent for injured children in our trial is consistent with prior literature. Approximately half of children with moderate-to-severe TBI do not have their guardian present in the ED in the first 3 h after injury [ 46 ]. Future work is planned to qualitatively and quantitatively evaluate parent or legal guardian perspectives regarding informed consent procedures for enrolling severely injured children into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, several randomized controlled trials in pediatric TBI investigating therapies such as hypothermia (102), decompressive craniectomy (103), or immune-enhancing diet (104), have failed to improve patient outcomes. Enrolling children in moderate to severe TBI trials has also been shown to be extremely challenging, due to heterogeneity of injury, early availability of guardians for informed consent, and the need for large number of centers requiring significant efforts in training and coordination (105). Using alternative approaches to randomized controlled trials, two large ongoing multicenter studies are starting to challenge paradigms of pediatric trauma systems and clinical care.…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%